Transformation from legacy storage to software defined storage–a review - Paul Chinnaraju, Swaraj; Gunasekaran, G; Kumar, N; Anandan, R (International Journal of Engineering and Technology, 2018)
In IT Industry the new trend is everything to be in Software defined. And so the storage industry has started its transformation from Legacy storage like storage area network and network attached storage. This is enable through the software defined networks. Software defined networks helps organizations to accelerate its application deployment, thus reducing IT costs by applying some policy enabled workflows. In this paper, we will have a review over the need for it from the storage vendor perspective.Â